Self-assembly in food — A concept for structure formation inspired by Nature. (March 2017) - Sagalowicz, Laurent; Michel, Martin; Blank, Imre; Schafer, Olivier; Leser, Martin E.
Abstract: Structures present in Nature have evolved over millions of years to achieve optimized functionalities. In the recent past, characterization techniques have been developed progressively allowing to better access and understand complex bio-architectures and structure–function relationships. Since in Nature energy is limited, weak interactions play a fundamental role for building supramolecular hierarchical structures. Self-assembly formation is a crucial process for building those complex architectures. In this article we will describe what types of structures are formed in Nature using the self-assembly concepts, and how those can be utilized to generate new benefits in food products. Our description will concentrate on examples where both self-assembled structure formation and functionality in food products are conceived and enhanced on inspiration by Nature. Our major interest here concerns the following architectures: 1) cell membranes formed mainly by phospholipids, 2) the phospholipid/protein membrane of oil bodies and 3) self-assemblies formed during lipid digestion. We will then explain how these self-assemblies are used both in Nature and food material science to obtain compartmentalization and structures for improved product performance regarding controlled release of aromas and nutrients, bioavailability, Maillard-type chemical reactions and chemical and physical stability. Such self-assemblies are present in many food products but could be much better used to create new benefits for the consumer. Graphical abstract: Highlights: Self-assembled structures provide functionality both in Nature and food products Understanding bilayer properties helps to comprehend the functions of cell membranes Self-assemblies are important during in-vitro lipolytic triglyceride digestion Self-assemblies enhance controlled release & bioavailability of nutrients Self-assemblies can provide chemical stability & control of Maillard-type reactions